Overview of the system-level anti-jamming capability and developmental challenges of low-earth-orbit signal-of-opportunity - Yao, Lihao; Fan, Bin; Qin, Honglei; Xian, Deyong; Wang, Mengli; Gu, Boyun; Chen, Sumin; Wang, Changhong; Wang, Xuyu; Shen, Jiemin; Jiang, Dongfang; Wei, Heng; et al. (Frontiers in Physics, 2025)
Signal-of-Opportunity (SOP) navigation based on Low-Earth-Orbit (LEO) satellite constellations has increasingly become a research hotspot. Due to the large number of LEO satellites, wide spectrum coverage, and strong signal power, LEO satellite Signal-of-Opportunity (LEO-SOP) inherently possess strong anti-jamming capabilities. However, there has been limited in-depth research on the overall system-level anti-jamming capability of LEO-SOP. This paper reviews the current state of research on LEO-SOP and anti-jamming technologies, introduces the principles of LEO-SOP Doppler-based positioning and receiver operation, and analyzes the system-level anti-jamming capability of LEO-SOP. Additionally, it explores the key challenges in the development of LEO-SOP anti-jamming technologies and discusses future research directions. This study aims to provide insights into the development prospects of LEO-SOP anti-jamming technologies, promote further research and development efforts, and establish a solid technical foundation for the secure application of LEO-SOP. Ultimately, ensuring the integrity and resilience of LEO-SOP systems against complex threats.